1996
DOI: 10.1121/1.416298
|View full text |Cite
|
Sign up to set email alerts
|

Speech versus nonspeech in pitch memory

Abstract: The memory trace of the pitch sensation induced by a standard tone (S) can be strongly degraded by subsequently intervening sounds (I). Deutsch [Science 168, 1604-1605 (1970)] suggested that the degradation is much weaker when the I sounds are words than when they are tones. In Deutsch's study, however, the pitch relations between S and the I words were not controlled. The first experiment reported here was similar to that of Deutsch except that the speech and nonspeech stimuli used as I sounds were matched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 17 publications
7
60
0
Order By: Relevance
“…Salame and Baddeley [1989] showed that vocal music interfered more strongly with phonological short-term memory than instrumental music, supporting the assumption of two independent WM systems for verbal and tonal stimuli [Salame and Baddeley, 1989]. On the other hand, results by Semal et al [1996] suggest that the pitch of speech sounds is not stored differently from the pitch of nonspeech sounds in WM. In addition, Iwanaga and Itoh [2002] reported that instrumental as well as vocal music interfered with a verbal WM task, and Chan et al [1998] observed that musical training increases the performance during a verbal WM task, suggesting rather overlapping neural resources for verbal and tonal WM.…”
Section: Introductionmentioning
confidence: 54%
“…Salame and Baddeley [1989] showed that vocal music interfered more strongly with phonological short-term memory than instrumental music, supporting the assumption of two independent WM systems for verbal and tonal stimuli [Salame and Baddeley, 1989]. On the other hand, results by Semal et al [1996] suggest that the pitch of speech sounds is not stored differently from the pitch of nonspeech sounds in WM. In addition, Iwanaga and Itoh [2002] reported that instrumental as well as vocal music interfered with a verbal WM task, and Chan et al [1998] observed that musical training increases the performance during a verbal WM task, suggesting rather overlapping neural resources for verbal and tonal WM.…”
Section: Introductionmentioning
confidence: 54%
“…Musicians relied more on a combination of encoding techniques (either dual or multiple), including auditory (tone sound), verbal (labeling tones or contour patterns), and tactile (playing an imaginary instrument) encoding, whereas nonmusicians relied suggest that acoustic similarity impacts upon nonmusicians' immediate serial recall of both verbal and tonal pitch materials. This correspondence suggests support for a degree of shared storage in short-term memory (Salamé & Baddeley, 1989;Semal et al, 1996). It is still possible to postulate the existence of separate stores for verbal and pitch sequences (Berz, 1995;Deutsch, 1970;Pechmann & Mohr, 1992) but with the caveat that they operate using similar principles (i.e., storage of pitch sounds).…”
Section: Resultsmentioning
confidence: 95%
“…Deutsch (1970) found that irrelevant tones disrupted performance on tone recognition, but that irrelevant speech materials had little if any detrimental effect. Since that study however, several authors have reported a significant effect of background speech and music on memory for musical sounds (D. M. Jones, Macken, & Harries, 1997;Pechmann & Mohr, 1992;Semal & Demany, 1991, 1993Semal, Demany, Ueda, & Hallé, 1996). Semal et al concluded that the pitch dimension, whether it be music based or speech based, is the element that is commonly disruptive to both verbal and musical processing in short-term memory.…”
mentioning
confidence: 98%
“…Although prior explanations of interference have advocated interitem confusion (e.g., Deutsch, 1984;Ruusuvirta et al, 2008), grouping (e.g., Jones et al, 1997), or general trace distortion (e.g., Semal et al, 1996) as the underlying causal mechanisms, TMM hypothesizes that interference results from feature overwriting and updating (McKeown & Wellsted, 2009;Mercer & McKeown, 2010). To test this possibility, listeners compared standard and comparison tones over a 10-sec interval.…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, it would appear that perceptually similar distractors can blur the memory of the standard, thereby distorting the accuracy of the trace (Pechmann & Mohr, 1992;Semal, Demany, Ueda, & Hallé, 1996), and Ruusuvirta et al (2002) have argued that the interfering tones bias the representation of the existing memory toward the frequency of the interfering event. Building on these ideas, Ruusuvirta et al (2008) asserted that interference is a consequence of interitem confusion.…”
mentioning
confidence: 99%